Peran Financial Technology, Literasi Keuangan, dan Inovasi Produk terhadap Kinerja Keuangan UMKM di Kabupaten Jepara - Nahar Rojab Surya Ningrum; Anna Widiastuti (IPB University, 2026)
The purpose of this study was to determine the role of financial technology, financial literacy, and product innovation in influencing the financial performance of MSMEs in Jepara Regency. This study employed a quantitative method, with primary data obtained through questionnaires. MSMEs in Jepara Regency served as the research population, and a sample of 140 respondents was selected. The sampling process used a non-probability sampling technique through purposive sampling. Data analysis utilized SEM-PLS. The results showed that financial technology and product innovation had a positive and significant effect on the financial performance of MSMEs in Jepara Regency, while financial literacy had no significant effect on the financial performance of MSMEs in Jepara Regency. This study demonstrates that the use of financial technology and the ability to innovate products are the main factors driving financial performance, while financial literacy has not yet had a significant impact because it has not been optimally implemented by business actors.